2009
DOI: 10.1016/s2255-4971(15)30045-8
|View full text |Cite
|
Sign up to set email alerts
|

Hip Arthroscopy in Athletes

Abstract: To confirm the therapeutic importance of hip arthroplasty in athletes whose pain precludes sportive function of the hip joint, being able to minimize it to the extent of helping on the return of sports practice at satisfactory levels. Methods: 49 athlete patients (51 hips) submitted to hip arthroscopy complaining of pain and inability to practice sports were assessed. Follow-up time ranged from 12 to 74 months (mean: 39.0 months). Preoperatively, pain site, severity according to Facial Expression Scale (FES) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 16 publications
(14 reference statements)
0
4
0
Order By: Relevance
“…5,9,13,14,30,32,33 Given the increasing volume of hip arthroscopy procedures being performed in athletes, data on the ability of athletes to return to sport (RTS) after hip arthroscopy have become more readily available. 1,[3][4][5][6][7][10][11][12][16][17][18][19][20][21][22][23][24][25][26][28][29][30][31][32][34][35][36][37] This information is critical, particularly for counseling patients, parents, and coaches on the expected outcomes after hip arthroscopy. While many of the available studies have focused on running and other highimpact and/or contact sports, there remains a paucity of data on the ability of patients to return to lower impact sports that require extremes of hip motion, including flexion and rotational loading.…”
mentioning
confidence: 99%
“…5,9,13,14,30,32,33 Given the increasing volume of hip arthroscopy procedures being performed in athletes, data on the ability of athletes to return to sport (RTS) after hip arthroscopy have become more readily available. 1,[3][4][5][6][7][10][11][12][16][17][18][19][20][21][22][23][24][25][26][28][29][30][31][32][34][35][36][37] This information is critical, particularly for counseling patients, parents, and coaches on the expected outcomes after hip arthroscopy. While many of the available studies have focused on running and other highimpact and/or contact sports, there remains a paucity of data on the ability of patients to return to lower impact sports that require extremes of hip motion, including flexion and rotational loading.…”
mentioning
confidence: 99%
“…Polesello et al 34 operated on 49 athletes (51 hips) and found that 76% of the athletes had fully returned to their sports after a minimum follow-up period of one year (mean of 39 months).…”
Section: Pathological Conditions Dealt With Using Hip Arthroscopymentioning
confidence: 99%
“…These mechanisms may include activities such as performing leg press exercises, ballet, yoga, spinning exercise, other gym activities, dancing, working in a squatting position and others. 24 , 25 , 26 , 27 , 28 …”
Section: Indicationsmentioning
confidence: 99%